Sposoby nobilitowania polityków w wybranych tekstach prasowych - Bryła, Władysława; Bryła-Cruz, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article deals with linguistic exponents of ennobling politicians in the press. The authors emphasize the coexistence of graphic elements (photos and colours) with verbal ones, i.e. lexis, grammatical categories and the following ways of argumentation: the legitimization of one’s own function, assuming the pose of dominance, steering a conversation and the functioning of the aureole effect.